2015
DOI: 10.1038/nature15539
|View full text |Cite
|
Sign up to set email alerts
|

Death from drought in tropical forests is triggered by hydraulics not carbon starvation

Abstract: 17Drought threatens tropical rainforests over seasonal to decadal timescales [1][2][3][4] , but the drivers 18 of tree mortality following drought remain poorly understood 5,6 . It has been suggested that 19 reduced availability of non-structural carbohydrates (NSC) critically increases mortality risk 20 through insufficient carbon supply to metabolism ('carbon starvation') 7,8 . However little is 21 known about how NSC stores are affected by drought, especially over the long term, and 22 whether they are mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
623
4
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 557 publications
(675 citation statements)
references
References 40 publications
33
623
4
15
Order By: Relevance
“…This behavior is contrary to the hypothesis, previously assumed, that the larger trees would be more resilient to droughts as a result of a deeper root system, allowing them to capture water from the deeper soil layers as a drought survival strategy. It was observed, however, that these large trees could be under water stress due to a significant exposure to solar radiation, eventually dying by cavitation and embolism (113) during extreme droughts.…”
Section: Impacts Of Anthropogenic Drivers Of Change In the Amazonmentioning
confidence: 99%
“…This behavior is contrary to the hypothesis, previously assumed, that the larger trees would be more resilient to droughts as a result of a deeper root system, allowing them to capture water from the deeper soil layers as a drought survival strategy. It was observed, however, that these large trees could be under water stress due to a significant exposure to solar radiation, eventually dying by cavitation and embolism (113) during extreme droughts.…”
Section: Impacts Of Anthropogenic Drivers Of Change In the Amazonmentioning
confidence: 99%
“…Finally,Eqs. (2a,2b) provides a testable hypothesis explaining why larger trees are more vulnerable to drought (Nepstad et al 2007) or have an apparently lower xylem P50 compared to smaller trees of the same species (Rowland et al 2015).…”
mentioning
confidence: 99%
“…This may provide an advantage during short-term droughts but not necessarily during longer, more intense drought events. The ability to moderate water uptake and growth may be absent in the tropics; Rowland et al [66] found no change in the growth rate of trees in the Amazon under a long-term drought.…”
Section: Figurementioning
confidence: 99%